Experimental-design Specific Changes in Spontaneous EEG and During Intermittent Photic Stimulation by High Definition Transcranial Direct Current Stimulation. (1st February 2020) - Lazarev, V.V.; Gebodh, N.; Tamborino, T.; Bikson, M.; Caparelli-Daquer, E.M.
Highlights: Active and Sham HD-tDCS affect EEG alongside time-dependent (no-stimulation) changes. tDCS experimental design and time-point comparisons affect EEG outcome measures. Focal HD-tDCS supports the investigation of lateralized EEG changes. EEG photic driving detects HD-tDCS effects more consistently than spontaneous EEG. Abstract: Electroencephalography (EEG) as a biomarker of neuromodulation by High Definition transcranial Direct Current Stimulation (HD-tDCS) offers promise as both techniques are deployable and can be integrated into a single head-gear. The present research addresses experimental design for separating focal EEG effect of HD-tDCS in the '4-cathode × 1-anode' (4 × 1) montage over the left motor area (C3). We assessed change in offline EEG at the homologous central (C3, C4), and occipital (O1, O2) locations. Interhemispheric asymmetry was accessed for background EEG at standard frequency bands; and for the intermittent photic stimulation (IPS). EEG was compared post- vs pre-intervention in three HD-tDCS arms: Active (2 mA), Sham (ramp up/down at the start and end), and No-Stimulation (device was not powered), each intervention lasting 20 min. The asymmetric background EEG changes were only in the central areas with right-side amplitude spectra prevalence, most pronounced in the no-stimulation arm, where they depended on comparison time-points and were consistent with markers of transition between drowsiness and vigilance – bilateral decrease in the delta and asymmetric central increase in the alpha and beta1 bands. For the active arm, similar but less pronounced changes occurred in the alpha band. In contrast, responses to IPS developed similar asymmetric amplitude increase at four harmonics of the IPS of 3 Hz only in the active arm, against a background of a brain-wide symmetric increase in both active and sham arms. Our protocols and analyses suggest methodological caveats for how EEG of tDCS studies could be conducted to isolate putative brain polarization outcomes.